Pembiasaan Tadadarrus Al-Qur’an Guna Memotivasi Siswa dalam Minat Belajar Al-Qur’an Hadist di MTs Miftahul Ilmiyah Mojowetan - Rahayu Novitasari, Ramadhani; Syaifulloh, Ahmad (Sekolah Tinggi Agama Islam (STAI) Khozinatul Ulum Blora, 2020)
This research is motivated by the reduced awareness of the Islamic community about the importance of learning, especially learning the Qur'an. In addition, their lack of knowledge about the Qur'an makes people reluctant to study it, even though the Qur'an is the main guideline for Muslims in carrying out life in the world. The Qur'an is the source of all knowledge in the world, both past and future lives. Therefore, there is nothing wrong with studying in depth about the Qur'an because the Qur'an never tells lies to Muslims. The focus of the research in this thesis is 1) How is the process of implementing the habituation of tadarus Al-Qur'an students at MTs Miftahul Ilmiyah Mojowetan? 2) How is the method of habituation of tadarus Al-Qur'an students at MTs Miftahul Ilmiyah Mojowetan? 3) Why is Al-Qur'an tadarus habituation held at MTs Miftahul Ilmiyah Mojowetan? The purpose of this study is to find out how students are accustomed to reading the Qur'an, the method in habituation to reading the Qur'an of students and why learning activities to read the Qur'an are held. In this study using the following research methods: 1) type or pattern of qualitative research, 2) data sources: resource persons, and school data, 3) data collection techniques are in-depth interviews, participant observation and documentation, 4) data analysis techniques are data reduction and drawing conclusions The results of this thesis research are 1) to carry out the habit of reading the Qur'an every morning for 15 minutes, for Friday to carry out khotmil Qur'an for the excellent class and for the regular class to read Surah Yasin, tahlil and istiqosah 2) for the method that uses used the punishment method, assignment method, peer tutor method, and classical method 3) for consideration that the habituation of reading the Qur'an is held is the positive impact that will be felt from reading the Qur'an is very large and as an effort to achieve the vision and mission school.